The narrative point of the novel of education of the twentieth century - Farrukh Kadirov; Umida Fayzullaeva (Zien Journals, 2022)
This article is dedicated to the narrative of the novel of upbringing includes various myths, stable literary and folklore motifs, and its structural analogy, one can assume, is the scheme of a fairy tale. There is a point of view associated with the fact that, in addition to texts directly focused on initiation, typologically comparable to it, the plot scheme of initiation in literature is artificially distinguished and is conditional, since it is more about the coincidence of a certain frame, universal laws of narration.
Keywords: narration; myth; universality; sacredness